Comparative Influence of Cohesion and Friction Angle on the Stability of Dry Slopes: A Parametric Sensitivity Study of Ramche Landslide (Pokhara Engineering College Journal, 2026)
The reliability and safety of slope designs largely depend on accurately understanding and measuring the soil properties of slope, because small errors in estimating this parameter can significantly affect stability predictions. This study investigates the sensitivity of slope stability to variations in cohesion (c) and internal friction angle (f) with respect to the Factor of Safety (FoS). The research focuses on the Ramche landslide in Rasuwa District, Nepal, representing a typical Himalayan slope condition. Six disturbed and undisturbed soil samples were collected from different locations along the slope profile during a detailed field investigation. Laboratory testing was conducted to determine key engineering properties, including cohesion, friction angle, and unit weight. Based on field measurements, slope geometry was prepared using AutoCAD and SW DTM software, and a numerical model was developed in Slide2. The soil behavior was simulated using the Mohr–Coulomb failure criterion. Slope stability was evaluated using four limit equilibrium methods: Bishop Simplified method, Janbu Simplified method, Spencer method, and Morgenstern–Price method. Sensitivity analyses, including tornado and spider plots, indicate that f is the most influential parameter, producing significantly greater variation in FoS compared to cohesion. The results consistently show that slope stability is more sensitive to uncertainties in the friction angle, highlighting the importance of accurate shear strength characterization for reliable slope design and risk assessment.